THE CONCEPT OF UNIFICATION OF TRUTH ACCORDING TO IBN RUSYD AND ISMAIL R. FARUQI: A STUDY BETWEEN REVELATION TEXT AND REALITY - Azfar, Fani; Yudela, Farida Wardah; Yudela, Farida Wardah (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This paper explores the integration of knowledge from various sources, particularly the interplay between divine revelation and empirical reality (reason). It delves into the concept of unifying truth as articulated by Ibn Rusyd and Ismail R. Faruqi, using case studies from Quranic verses such as AlKahfi: 95-98 and Al-Ankabut: 45 to examine potential paradoxes between religious texts and observable reality. The research employs a qualitative descriptive approach, focusing on library research. The findings suggest that knowledge derived from divine revelation can be strengthened and enriched by empirical evidence. This is exemplified by the Quranic reference to the strength of iron and copper, which, when subjected to empirical testing, yielded valuable insights into their properties. The paper argues that when knowledge from divine revelation and empirical sources align, they validate each other and contribute to a deeper understanding of truth. However, when contradictions arise between these two knowledge sources, the authors propose two approaches. Ibn Rusyd recommends relying on rational argumentation and interpretation by experts to resolve such conflicts. Ismail R. Faruqi, on the other hand, advocates for objective data review and re-evaluation of interpretations, allowing for a more nuanced understanding. In conclusion, the integration of knowledge from various sources necessitates a measured and open-minded approach. Rushing to create paradoxical justifications should be avoided, and it is essential to reevaluate our understanding of both divine texts and empirical data. Open-mindedness is crucial to reconciling the relationship between divine revelation and reality, recognizing that all truth ultimately derives from the same source: God. This study contributes to the ongoing dialogue on the integration of knowledge, emphasizing the importance of harmonizing diverse sources of knowledge for a comprehensive understanding of truth.